GIARDIASIS IN CHILDREN AND ITS SIGNIFICANCE IN THE ETIOPATHOGENESIS OF DISEASES IN CHILDREN - Ibatova Sh.M., Mamatkulova F.Kh., Normakhmatov B.B. (American Journals Publishing, 2023)
Giardiasis is one of the most common helminthic infestations in the world. The problem of giardiasis is also very relevant for Uzbekistan. In Uzbekistan, among parasitic diseases, giardiasis accounts for a large proportion (60-70%) of children in organized children's groups [1-5]. The discussion about the pathogenicity of Giardia, which lasted for a long time, can be said to have ended with the recognition of their damaging effect on the villi of the intestinal epithelium, where they vegetate [10]. According to the conclusion of the WHO expert group, Lamblia intestinalis should be considered a pathogenic protozoan [6-9].